Analisis Dampak Pengelolaan Dana Desa terhadap Peningkatan Kesejahteraan Masyarakat Pesisir melalui Program Pemberdayaan Perempuan Nelayan: Studi Kasus Desa Domas, Kabupaten Serang - Ria Amelia; Laeli Nur Khanifah; Yolanda Mazmuria Manurung; Azalia Salsabila; Minerva Laisa Sabatini (Jurnal Media Administrasi, 2025)
In this study, a women's empowerment program for fisherwomen in Domas Village, Serang Regency, was used to investigate the impact of village fund management on improving the welfare of coastal communities. This research stems from an awareness of the importance of villages in realizing sustainable development that relies on local potential, especially in vulnerable and marginalized coastal areas. To improve community welfare, including that of women who have been less involved in village development processes, effective, efficient, transparent, and accountable management of village funds is crucial. The research method employed was qualitative, with data collected through in-depth interviews, field observations, and documentary studies. The research results show that the management of village funds in Domas Village has brought many benefits, such as the establishment of BUMDes shrimp farms and catering services, which can create jobs and increase local revenue. However, women's participation in village programs is still limited to certain industries such as beauty services and seafood processing. To achieve optimal women's empowerment, key barriers include limited human resources, limited access to capital, and the lack of integration of women's SMEs into the village funding structure. The results indicate that an inclusive and locally-driven approach to village fund management can enhance community well-being more equitably and drive sustainable socio-economic transformation.